PENERAPAN AJARAN TASAWUF-TAREKAT DI PONDOK PERSULUKAN (PONSLUK) DARUSSOUFIYAH DESA HUTA LOMBANG KECAMATAN PADANGSIDIMPUAN TENGGARA (Suatu Tinjauan Aplikatif Metodologis) Oleh : - Hasibuan, Armyn (Institut Agama Islam Negeri Padangsidimpuan, 2014)
AbstractThis Collective research is descriptive research qualitative aim to see to near from applying of teaching of tasawuf-tarekat in The Maisonette of Persulukan (Ponsluk) Darussoufiyah Countryside of Huta Lombang District of Padangsidimpuan South-East as one of the institute education of religious nonformal continual in guiding all